Modelling and experimental study of a microforging process from metal strip for the reduction of defects in mass production - Stellin, Tommaso; Van Tijum, Redmer; Engel, Ulf (Production Engineering, 2016)
Microforming from sheet metals is a technology with high potential and increasing interest in modern factories. The combination of bulk forming technologies in micro-scale together with the easier handling of metal strips allows the high rate production of products with small dimension and is suited for commercial fields like electronics and micromechanics. The need of an efficient FEM aided process design must face the problem of material behavior in microforming, affected by size-effects and not obeying continuum mechanics. A reliable FE model allows the production of a database allowing, additional to process optimization, the design of online process control and the reduction of manufacturing defects, strongly affecting micro-productions because of the high deviations in such processes. In this work, a method for the design of a FEM model of a microforging process is proposed, developed in the commercial software MSC Marc including the modelling of local size effects in the form of variable friction. An increased friction factor is assumed, where typical microforming size effects are expected to take place. Stainless steel and copper-beryllium alloys are studied with the thickness of 300 µm. The microforged geometry consists in 6 parallel protrusions with a width of 200 µm. The experimental study is then performed, by varying punch forces, firstly in a simplified configuration with two protrusions and finally with the complete geometry in a multi-stage microforming process, respectively validating and verifying the developed simulation model.
LFT Import::2019-07-29 (2163)
Keywords: Copper-beryllium; Microforming; Numerical simulation; Sheet-bulk forming; Stainless steel